2017
DOI: 10.1007/s00264-017-3562-7
|View full text |Cite
|
Sign up to set email alerts
|

Locking screw-plate interface stability in carbon-fibre reinforced polyetheretherketone proximal humerus plates

Abstract: The mechanical stability of locking screws in CFR-PEEK plates is comparable or superior to locking screws in SS plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…According to biomechanical studies, fixation of unstable proximal humerus fractures with a CFR-PEEK plate allows an increased motion at the bone-implant interface compared with a titanium locking plate, which might be an advantage [23,33]. Another biomechanical study showed an equal or higher stability of locking screws in CFR-PEEK plates compared to locking screws in stainless steel plates [15]. There are several clinical studies in the literature that analyzed both the functional results and unfavorable events after angular stable plate fixation of the proximal humerus.…”
Section: Unfavorable Events and Revisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to biomechanical studies, fixation of unstable proximal humerus fractures with a CFR-PEEK plate allows an increased motion at the bone-implant interface compared with a titanium locking plate, which might be an advantage [23,33]. Another biomechanical study showed an equal or higher stability of locking screws in CFR-PEEK plates compared to locking screws in stainless steel plates [15]. There are several clinical studies in the literature that analyzed both the functional results and unfavorable events after angular stable plate fixation of the proximal humerus.…”
Section: Unfavorable Events and Revisionsmentioning
confidence: 99%
“…The CFR-PEEK plates have a modulus of elasticity that is very similar to that of cortical bone [ 33 ]. Biomechanical studies showed several advantages like an increased motion at the bone-implant interface and a higher stability of locking screws in the CFR-PEEK plates [ 15 , 22 , 34 ]. Locking titanium plates have a rigid link between plate and screw, which can lead to failure at the bone-screw interface, especially in osteoporotic bone [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This technique can yield positive results, especially in fracture types with large and strong nodular fracture fragments. After the introduction of locking steel plates, the indications for such treatment increased [22]. Traditionally, at the metaphysis with poor proximal humerus, screw fixation carries the risk of screw detachment.…”
Section: Internal Fixation Therapymentioning
confidence: 99%
“…CF-PEEK plates demonstrated similar mechanical properties to that of titanium plates, except for bending strength, inferior by 20% to that of a metal proximal humerus plate, and yet adequate for proximal humerus fixation, with the advantage of decreased debris particles formation 84,85 . Its increased flexibility may exert a positive effect on fracture healing 87 ; its elastic modulus should unload the screw-tip/bone interface and therefore lower the rate of secondary screw perforation and loss of reduction 88 . The radiolucency grants an easier intraoperative fluoroscopic evaluation of fracture reduction and greater tuberosity position and a clearer post-operative radiographic assessment of reduction loss and fracture healing (Fig.…”
Section: Cf-peek Platesmentioning
confidence: 99%
“…Due to the difference in material composition, cold welding between plate and screws is avoided, allowing easier and safer hardware removal 83 . Locking screws of CF-PEEK plates can cut-through plate material, tapping their thread, or can lock to pre-machined threads in the plate holes 87 . No changes in biomechanical properties of the plate was detected depending on plate/screw interface 86 .…”
Section: Cf-peek Platesmentioning
confidence: 99%